Thermophysical evaluation of nanocellulose as a new coolant for radiator - Ganesan, Kadirgama (2018)
Nanocellulose with water and Ethylene Glycol addition to coolant for car radiator application has benefits of improving the efficiency of the radiator. Improved efficiency of the coolant leads to the more compact design of the radiator due to less area required. The research is conducted to prove that addition of nanocellulose originating from plant base with varying concentration provides a better heat transfer efficiency compared to the usage of water as radiator coolant. The objective of the research is to improve and create a new radiator coolant based on the collaboration of nanocellulose with readily available coolants which is Ethylene Glycol. The main scopes of the research are the nanocellulose between ranges of size 35-39 nm. The tested concentration of the cellulose nanofluids are in of 0.1%, 0.5%, 0.9% and 1.3%. The preparation of cellulose nanofluids is carried out at Advance Automotive Liquid Lab (A2LL) of Universiti Malaysia Pahang. Analysis of statistical tool shows that volume concentration 0.5% has an optimized thermophysical property and it can function as nanofluid (thermal transport fluid) in the radiator. Then, the experiment for heat transfer performance comparison for nanofluid and conventional thermal transport fluid flows in the automotive radiator test rig. Experiment for heat transfer analysis of thermal flow varies with the flow rate. The experimental result shows that heat transfer coefficient, convective heat transfer, Reynolds number, the Nusselt number has proportional relation with volumetric flow rate. Meanwhile, friction factor has an inverse relation with the volumetric flow rate. The result, after running the radiator test rig with 0.5% volume concentration of distilled water and Ethylene Glycol nanofluid shows there is a significant change in the difference between inlet and outlet temperature of the fluid flowing through radiator test rig. Besides, from the thermal conductivity data, it shows thermal conductivity increases from 0.487 W/m. °C at 30°C to 0.532 W/m. °C at 70°C while the viscosity decreases from 15.01 m.Pa.s at 30°C to 1.77 m.Pa.s at 70°C. Thus, nanofluid able to remove heat efficiently in the automotive cooling system. Thus, nanocellulose based nanofluid is suitable for automotive cooling application since it has a better heat transfer performance than conventional thermal transport fluid.